Stroke lesions and post-stroke depression among survivors in Ibadn, Nigeria (2013)
"Background: We aimed to determine the association between the neuro-radiological characteristics of stroke lesions and post-stroke major depression among survivors in Ibadan, Nigeria. This is in the background of a paucity of information on the clinico-pathological correlation of post-stroke emotional responses among African Survivors. Method: We studied 30 stroke survivors receiving physiotherapy. The radiological characteristics of the stroke lesions were documented using computerized tomography or magnetic resonance imaging scans in the acute phase of the stroke. While the presence of major depressive disorder meeting criteria in the fourth edition of the Diagnostic and Statistical Manual was assessed using the Schedule for Clinical Assessment in Neuropsychiatry (SCAN), between 3 months and 2 years after. The association between lesion characteristics and depression was explored using logistic regression analysis. Result: Nine (30.0%) stroke survivors met criteria for major depressive disorder. There were significant differences in their gender. The differences in the lesion types approached the set level of significance in survivors with or without major depressive disorder. There were however no differences when considering hemispheric lateralization or intrahemispheric lesion location. Being female, but not the lesion characteristics was strongly associated with post-stroke major depressive disorder. Conclusion: Lesion characteristics documented in the acute phase of stroke could not predict the occurrence of majbr depressive disorder during rehabilitation in this sample. The occurrence of depression among stroke survivors may ultimately be determined by a combination of factors. "